Intention to Preach for Wildlife Protection in Sumatra Indonesia - Praharawati, Gugah; Mardiastuti, Ani; Masy'ud, Burhanuddin; Sunito, Satyawan; Mangunjaya, Fachruddin Majeri (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
This study analyzes the involvement of Clerics at the grassroots that help the implementation of the MUI Fatwa No 4/2014 regarding protected wildlife for the balance of the ecosystem. This study measures their knowledge-attitude-practice (KAP) and intentions to preserve nature and wildlife in conservation areas. The Clerics were invited from 11 villages surrounding Rimbang Baling Wildlife Sanctuary (RBWS), Riau. The clerics strengthened and trained to understand Islamic conservation ethics, accepting the fatwas and intensive guidance and information on da'wah, then tested using questionnaires before and after the training. The survey was conducted by providing 15 question indicators. ANOVA test results showed that the pre-test and post-test had significant F test results, with a sig value < 0.05. The relationship between attitudes, norms, behavior, and knowledge to conserve wildlife before training was R = 0.547 and after training was R = 0.662. The variables affect wildlife conservation actions by 37.4%.